SEHAT: Teknik Praktis untuk Melepaskan Stres Karir dan Membangun Kualitas Hidup di Komunitas Oshibana NaraArt Bekasi - Gutara, Mohamad Yudha; Rizanty, Rahmadhania; Kiranida, Oktafiana; Wati, Dian Eka; Tatavianola, Avsah (Universitas Pahlawan Tuanku Tambusai, 2025)
Career stress often emerges subtly, undermining motivation and diminishing quality of life, particularly among university students, fresh graduates, and individuals in transition to the workforce. Many feel trapped between social expectations, unclear goals, and anxiety about the future. Unfortunately, few know simple yet effective ways to cope with such pressure. This community service activity introduced the SEHAT (Self Emotional Healing Therapy) technique, a practical approach combining mindfulness, journaling, positive affirmations, and reflective discussion. Conducted on July 8, 2025, at Cafe Omah Dulang, East Jakarta, the workshop engaged 25 participants from diverse backgrounds, including teachers, social activists, students, parents, and community members. Evaluation results indicated that participants not only understood the material but were also able to practice the SEHAT techniques and expressed their commitment to applying them and supporting others. These findings demonstrate that SEHAT is an effective and accessible strategy for enhancing emotional regulation, resilience, and career readiness.